Practices and knowledge on primary prevention of tuberculosis in university students of health sciences in Tacna, Perú - Quispe-Prieto, Silvia (2019)
Introduction. The tuberculosis (TB) is an occupational risk for health workers and health careers students. Objetives: To describe the practices and knowledge about primary prevention of TB in health sciences students, also we identified the associated factors to prevention practices. Methods. We performed a cross sectional study in health careers students of penultimate year of four universities in the city of Tacna. In 2018, we applied a questionnaire that included 16 questions about knowledge and 13 about TB prevention practices. We performed a descriptive analysis for practices and knowledge, in addition the factors associated with the practice score were determined with a linear regression analysis. Results. 264 students participated. Regarding the use of the N95 respirator, 60,3% say that they always use it when interacting with TB patients. The university career (β: -1,23, 95% CI: -1,98 to -0,48) and the previous practices in emergency services (β: 3,08, 95% CI: 0,618 to 5,541) were associated with score for TB prevention practices. Conclusion. Exist an important gap in knowledge and practices about primary prevention of TB in students before starting internship.